1992
DOI: 10.1073/pnas.89.23.11229
|View full text |Cite
|
Sign up to set email alerts
|

High density of Ca(2+)-dependent K+ and Cl- channels on the luminal membrane of lacrimal acinar cells.

Abstract: Tight-seal whole-cell recording and Ca2+ uMaging were simultaneously performed on cell dusters or individual acinar cells of rat lacrimal glands during appliction of the secretagogue acetylcholine. Activation of 2+-dependent K+ and Cl-currents was selectively followed as a f i of time by placing the cell potential near the equilibrium potential for Cl-or for K+ ion, respectively. Upon acetylcholine application to cel clusters, K+-and a--selective currents displayed a distinctive initial rise ("hump"). At this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 26 publications
(23 reference statements)
2
26
1
Order By: Relevance
“…It is interesting to note that rises in Ca2+ which lead to vesicle fusion may be mediated by Ca2+ release from organelles in the granular area (Marty, 1991). In fact, increases in [Ca2+]i always started at the granular area where secretory granules lie (Kasai and Augustine, 1990;Nathanson et al, 1992;Tan et al 1992;Toescu et al, 1992 Our study demonstrated that exocytotic secretion could be triggered directly by individual Ca2+ spikes, because exocytotic fusion was less sensitive to Ca2+, and because Ca2+ spikes were sufficient for triggering exocytotic fusion.…”
Section: Introductionmentioning
confidence: 86%
“…It is interesting to note that rises in Ca2+ which lead to vesicle fusion may be mediated by Ca2+ release from organelles in the granular area (Marty, 1991). In fact, increases in [Ca2+]i always started at the granular area where secretory granules lie (Kasai and Augustine, 1990;Nathanson et al, 1992;Tan et al 1992;Toescu et al, 1992 Our study demonstrated that exocytotic secretion could be triggered directly by individual Ca2+ spikes, because exocytotic fusion was less sensitive to Ca2+, and because Ca2+ spikes were sufficient for triggering exocytotic fusion.…”
Section: Introductionmentioning
confidence: 86%
“…Cook and colleagues (5, 6) hypothesized that fluid secretion can be driven by K channels in the apical membrane of acinar cells. In fact, there is direct evidence for an apical maxi-K-like current in the acinar cells of frog skin (41) and for apical Ca 2ϩ -activated K ϩ currents in rat lacrimal acinar cells (44 (30,50). Because the K ϩ and Na ϩ concentrations of both the acinar secretions and the venous plasma outflow from salivary gland (which reflects the interstitial ion concentration) are plasma-like, this suggests that K ϩ and Na ϩ likely enter the primary saliva across the "leaky" tight junctions of the acinus.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kasai & Augustine (1990) reported that in rat pancreatic acinar cells they were localized at the apical end of the cell. More recently, Ca2+ release has been shown to occur at the apical pole of mouse pancreatic and lacrimal acinar cells (Toescu, Lawrie, Petersen & Gallacher, 1992) and of rat lacrimal acinar cells (Tan, Marty & Trautmann, 1992). In rat parotid acinar cells, the elevation of [Ca2+]i resulting from stimulation of muscarinic receptors induces both an outward current, carried mainly by K+ ions through Ca2+-activated K+ channels, and an inward current, carried mainly through Ca2'-activated Cl-channels (Iwatsuki, Maruyama, Matsumuto & Nishiyama, 1985;Gray, 1988a).…”
mentioning
confidence: 99%